2016
DOI: 10.3390/v8030055
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparison of Receptor Binding Characteristics of the Spike Protein of Two Porcine Epidemic Diarrhea Virus Strains

Abstract: Porcine epidemic diarrhea virus (PEDV), a member of Alphacoronavirus, has caused huge economic losses for the global pork industry recently. The spike (S) protein mediates PEDV entry into host cells. Herein, we investigated the interactions between the S protein and its receptor porcine aminopeptidase N (pAPN) or co-receptor sugars. The C-terminal domain (CTD) of the S1 domain is bound to pAPN. The prototype strain demonstrated similar receptor-binding activity compared with the variant field isolate. Three lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 38 publications
3
104
0
1
Order By: Relevance
“…This indicated that VN297/HB/2013 might also possess the same 72‐nucleotide deletion in ORF1a compared with HUA‐14PED96, although more extensive genome sequencing is required to clarify this finding. In this study, we identified one novel PEDV strain, VN‐TH15/HY/2015, with an 8‐amino acid insertion between positions 380 and 381 of the S protein, which are located in the receptor‐binding domain (amino acids 253–638) for porcine aminopeptidase N (Liu et al., ; Deng et al., ). It is revealed that the classical PEDV exhibited weaker sugar‐binding activity than the recently uncovered G2 isolates (Deng et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that VN297/HB/2013 might also possess the same 72‐nucleotide deletion in ORF1a compared with HUA‐14PED96, although more extensive genome sequencing is required to clarify this finding. In this study, we identified one novel PEDV strain, VN‐TH15/HY/2015, with an 8‐amino acid insertion between positions 380 and 381 of the S protein, which are located in the receptor‐binding domain (amino acids 253–638) for porcine aminopeptidase N (Liu et al., ; Deng et al., ). It is revealed that the classical PEDV exhibited weaker sugar‐binding activity than the recently uncovered G2 isolates (Deng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified one novel PEDV strain, VN‐TH15/HY/2015, with an 8‐amino acid insertion between positions 380 and 381 of the S protein, which are located in the receptor‐binding domain (amino acids 253–638) for porcine aminopeptidase N (Liu et al., ; Deng et al., ). It is revealed that the classical PEDV exhibited weaker sugar‐binding activity than the recently uncovered G2 isolates (Deng et al., ). Amino acid substitutions were also reported in the receptor‐binding region (Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Neu5Ac presented the highest binding affinity with PEDV S1 in experiments using a glycan array screening. Moreover, the sialic acid binding region of PEDV was confirmed as being in the NTD of the S protein (residues 1-320), similar to other CoVs [21]. However, it is unknown how the binding of sialic acid to the S protein can affect PEDV entry into cells.…”
Section: Sialic Acid Promotes Tgev and Pedv Binding To Host Cell Recementioning
confidence: 80%
“…Sequence analyses of PEDV prototype and variant strains reveal that the N terminus of the S protein changes more easily than the C terminus. In addition, a previous report suggested an interaction of NTD of the S1 domain with a coreceptor [20,21]. Simplified graphic of the structural domains of the main coronaviruses' spike proteins.…”
Section: The Role Of the Spike Protein Of Tgev And Pedvmentioning
confidence: 95%
See 1 more Smart Citation